2019
DOI: 10.1111/jcmm.14742
|View full text |Cite
|
Sign up to set email alerts
|

Toll‐like receptor 4 regulates spontaneous intestinal tumorigenesis by up‐regulating IL‐6 and GM‐CSF

Abstract: Inflammation is as an important component of intestinal tumorigenesis. The activation of Toll‐like receptor 4 (TLR4) signalling promotes inflammation in colitis of mice, but the role of TLR4 in intestinal tumorigenesis is not yet clear. About 80%–90% of colorectal tumours contain inactivating mutations in the adenomatous polyposis coli (Apc) tumour suppressor, and intestinal adenoma carcinogenesis in familial adenomatous polyposis (FAP) is also closely related to the germline mutations in Apc. The ApcMin/+ (mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 38 publications
2
22
0
Order By: Relevance
“…Corticotrophin-releasing hormone (CRH)/CRHR1 [140] KIOM-MA/MA128 [141] [herbal] Toll-like receptor 4 [142] Cocoa [143] Sonic hedgehog (SHH) signaling [144] IL-6 monoclonal antibody (mAb) [145] Probiotic agent VSL#3 [146]; Balsalazide (BSZ) [146] Based on the fact that some typical symptoms in PD like increasing colon transit time and constipation [147] resemble those in IBD, indicating the deficits in the intestinal immune barrier, and that some of them appear even earlier in the intestine than the motor ones finally manifest, researchers postulated the existence of brain-gut-axis modulation system in PD [148]. Also concerning the direction by which the disease spreads, two views exist among scholars, which are from brain to the gut or vice versa [149].…”
Section: Being Associated With Parkinson's Diseasementioning
confidence: 99%
“…Corticotrophin-releasing hormone (CRH)/CRHR1 [140] KIOM-MA/MA128 [141] [herbal] Toll-like receptor 4 [142] Cocoa [143] Sonic hedgehog (SHH) signaling [144] IL-6 monoclonal antibody (mAb) [145] Probiotic agent VSL#3 [146]; Balsalazide (BSZ) [146] Based on the fact that some typical symptoms in PD like increasing colon transit time and constipation [147] resemble those in IBD, indicating the deficits in the intestinal immune barrier, and that some of them appear even earlier in the intestine than the motor ones finally manifest, researchers postulated the existence of brain-gut-axis modulation system in PD [148]. Also concerning the direction by which the disease spreads, two views exist among scholars, which are from brain to the gut or vice versa [149].…”
Section: Being Associated With Parkinson's Diseasementioning
confidence: 99%
“…KEGG analysis found that cytokine-cytokine receptor interaction, chemokine signaling pathway, and MAPK signaling pathway were significant pathways. Cytokine-cytokine receptor interaction was related to the viability of colon cancer cell lines [29]. Besides, previous studies have demonstrated that abnormally activated MAPK pathway is closely associated with growth and metastasis of colon cancer [30,31].…”
Section: Discussionmentioning
confidence: 94%
“…The TruSeq Stranded mRNA LT Sample Prep Kit (Illumina, RS-122-2101) was used for the construction of 18 cDNA libraries [ 24 ], and the Illumina sequencing platform (HiSeqTM 2500) was used to sequence these libraries, generating 125 bp paired-end reads [ 25 , 26 ]. Raw data underwent recognition analysis to obtain original sequencing.…”
Section: Methodsmentioning
confidence: 99%